Muhammadiyah Dan Warisan Pemikiran Muhammad Abduh: Ikhtiar Merawat Nilai-Nilai Islam Berkemajuan - Ach Fuad Fahmi Adnan; SJ Fadil; Isroqunnajah Isroqunnajah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2025)
Muhammadiyah is one of the largest Islamic organizations in Indonesia and has played a crucial role in the modernization and reform of Islam. The movement is deeply rooted in the ideas of Muhammad Abduh, an Islamic reformer from Egypt who emphasized rationality, ijtihad, and education as the foundations of Islamic progress. This study aims to analyze the relationship between Abduh’s intellectual legacy and the concept of Progressive Islam promoted by Muhammadiyah. Using a qualitative library-based research method, this study finds that Muhammadiyah has adopted and further developed Abduh’s ideas, particularly in the fields of education, religious rationality, and social empowerment. Muhammadiyah promotes modern education that integrates religious and general sciences, encourages reason-based Islamic thought grounded in authentic texts, and actively engages in social programs to enhance public welfare. The study also identifies globalization and rapid social change as major challenges in maintaining the relevance of Progressive Islamic values. Therefore, continuous innovation in da‘wah and educational strategies is essential for Muhammadiyah to remain a progressive and competitive Islamic movement. This research contributes to a deeper understanding of Muhammadiyah’s role in sustaining a dynamic, rational, and modern Islamic tradition inspired by Muhammad Abduh.